Comparison of Two Main Orthokeratology Lens Designs in Efficacy and Safety for Myopia Control - Lu, Weiwei; Ning, Rui; Diao, Kai; Ding, Yang; Chen, Ruru; Zhou, Lei; Lian, Yan; McAlinden, Colm; Sanders, Francis W. B.; Xia, Fangfang; Huang, Jinhai; Jin, Wanqing (Frontiers in Medicine, 2022)
Purpose This study aimed to compare the efficacy and safety of corneal refractive therapy (CRT) lenses and vision shaping treatment (VST) lenses for myopia control in children. Methods Medical records of 1,001 children (2,002 eyes) who had been fitted with orthokeratology lenses for over 1.5 years were retrospectively reviewed. We collected the clinical data of four types of orthokeratology (OK) lenses available: one CRT lens (brand: CRT) and three VST lenses (brands: Euclid, Alpha, and Hiline) over 1.5 years. Results were compared and analyzed using a one-way ANOVA and Pearson's chi-square test. Results Axial length elongation in the CRT lens group was 0.13 ± 0.02 mm faster than that in the Euclid lens, 0.1 ± 0.02 mm faster in the Alpha lens, and 0.08 ± 0.02 mm faster in the Hiline lens over the 1.5-year period (all P < 0.05). Among the subjects, 37.3% of them using the CRT lens experienced more than 1 D of refractive growth, compared with 20.2–30.8% of subjects wearing the three groups of VST lenses (all P < 0.05). A lower incidence of total adverse events was found with the CRT lenses compared with the VST lenses (P < 0.05), especially corneal staining. No difference was found in axial length elongation, refraction growth, and incidence of adverse events among the three types of VST lenses (all P > 0.05). Conclusions Compared with the VST lenses, CRT lenses demonstrated a weaker effect on myopia control but with a better safety profile. Different types of VST lenses had similar efficacy and safety in the context of controlling myopia progression.